Resilience and the Rapid Shift to Remote Working at a University: Emerging Questions - Lustig, Caitlin; Hoy, Josephine; Alimohammadi, Negin; Jones, Ridley; Lee, Charlotte P. (2020)
ABSTRACT We describe work-in-progress for a qualitative, interview-based study of organizational resilience at a large research university during the unfolding crisis of the COVID-19 pandemic. This paper discusses example data and questions raised by interviews of participants that represent a wide variety of roles, contexts, and challenges. Our ongoing data collection shows participants navigating different ways of enacting resilience in their attempts to weather the rapid changes to their work and organizations brought on by COVID-19. This preliminary work already raises questions about how organizational resilience is enacted, how the boundaries of formal organizations are being redefined, and work activities are being reorganized. These themes lay groundwork for future studies of organizational and system resilience during long-term crises. Keywords resilience, CSCW, organizational theory, infrastructure studies, coordination ABOUT THE AUTHOR/S Caitie Lustig University of Washington celustig@uw.edu Ridley Jones University of Washington rajone@uw.edu Josephine Hoy University of Washington joeyhoy@uw.edu Negin Alimohammadi University of Washington negin@uw.edu Charlotte P. Lee University of Washington cplee@uw.edu Josephine Hoy, Caitlin Lustig, Negin Alimohammadi, and Ridley Jones are PhD students in the Computer Supported Collaboration (CSC) Laboratory, which is directed by Prof. Charlotte P. Lee. We conduct empirical research on how people collaborate in everyday practices, in order to develop principled approaches to the design of collaborative systems and organizations. CSC is in the Department of Human Centered Design & Engineering at the University of Washington. https://depts.washington.edu/csclab New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).